1984
DOI: 10.1172/jci111385
|View full text |Cite
|
Sign up to set email alerts
|

Defective beta adrenergic response of cystic fibrosis sweat glands in vivo and in vitro.

Abstract: Abstract. Abnormal ductal NaCi absorption has been known as the only defect in cystic fibrosis (CF) sweat glands. We have fortuitously found that the secretory portion of CF sweat glands is also abnormal in that it failed to show a sweating response to beta adrenergic stimulation (isoproterenol, [ISO]) both in vivo and in vitro. For the in vitro sweat test, eccrine sweat glands were isolated from skin biopsy specimens of the forearm, cannulated, and stimulated to secrete sweat. All 14 isolated CF sweat glands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
1
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(173 citation statements)
references
References 14 publications
9
162
1
1
Order By: Relevance
“…In addition, intracellular chloride is significantly (P < 0.00009; t test) higher in hypertension. This is consistent with an increase in the activity of the co-transporter, resulting also in the depolarization of membrane potential which we have reported previously (Davis et al 1991 (Sato & Sato, 1984;Bovell et al 1989). In the present experiments we have explored the extent to which such second messenger signals can be evoked in primary cultures of sweat gland epithelial cells (Lee et al 1986) and in a permanent cell line (NCL-SG3) derived from such cells by SV40 transformation (Lee & Dessi, 1989).…”
Section: ±3supporting
confidence: 83%
“…In addition, intracellular chloride is significantly (P < 0.00009; t test) higher in hypertension. This is consistent with an increase in the activity of the co-transporter, resulting also in the depolarization of membrane potential which we have reported previously (Davis et al 1991 (Sato & Sato, 1984;Bovell et al 1989). In the present experiments we have explored the extent to which such second messenger signals can be evoked in primary cultures of sweat gland epithelial cells (Lee et al 1986) and in a permanent cell line (NCL-SG3) derived from such cells by SV40 transformation (Lee & Dessi, 1989).…”
Section: ±3supporting
confidence: 83%
“…USA 82 (1985) 6171 regulation may be faulty. A defect in regulation is suggested by the results of Sato and Sato (19). They found that methacholine induced the same flow rates from normal and CF sweat glands and that isoproterenol caused the same elevation of cyclic AMP in control and CF glands and stimulated sweat secretion in normal glands but did not induce flow from CF glands.…”
Section: Discussionmentioning
confidence: 93%
“…The protocols were designed to give the most reproducible results in each case, but they have the drawback that comparisons of sweat responses are strictly relative to our procedures: absolute sweat rates, including maximal rates, were not measured. For 0-adrenergic stimulation, sweat was collected once, 40 min after stimulation, to maximize the amount of sweat obtained in each test (most sweating t o P-adrenergic stimulation occurs in the first 20 min following an injection, and is virtually complete after 30 min) (8).…”
Section: Glandsmentioning
confidence: 99%